2018
DOI: 10.1016/j.jaip.2017.12.033
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Self-Reported Penicillin Allergy: A Systematic Review

Abstract: Evaluations of clinical and economic outcomes of PCN allergy are primarily observational and focus on inpatient populations. Long-term relationships between PCN allergy and clinical and economic outcomes are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 33 publications
4
79
0
Order By: Relevance
“…It has been considered that a correct diagnosis could save around 1145-4254$ per patient. 20,21 Over recent years, mislabelling is showing to be a relevant problem in two ways: (a) false label of allergic, which increment the real DHR incidence and affect the individual treatment options; (b) false In this review, we have considered these problems highlighting the recent advances about risk factors, diagnostic approaches, mechanisms involved as well as prevention actions, and management.…”
Section: The Burden Of Drug Hyper S En S Itivit Ymentioning
confidence: 99%
“…It has been considered that a correct diagnosis could save around 1145-4254$ per patient. 20,21 Over recent years, mislabelling is showing to be a relevant problem in two ways: (a) false label of allergic, which increment the real DHR incidence and affect the individual treatment options; (b) false In this review, we have considered these problems highlighting the recent advances about risk factors, diagnostic approaches, mechanisms involved as well as prevention actions, and management.…”
Section: The Burden Of Drug Hyper S En S Itivit Ymentioning
confidence: 99%
“…Inappropriate allergy labels result in increased healthcare costs and adverse events. 16,17 Our results show that more than 85% of penicillin allergy labels in our patient group were incorrect. This finding is consistent with those of other reports 2,5 and supports the need for allergy evaluation services in our healthcare system.…”
Section: Discussionmentioning
confidence: 69%
“…In a retrospective study at a Veterans Affairs hospital, patients with a penicillin allergy had a significantly longer time to receipt of first antibiotic dose (236 minutes vs 187 minutes, P = .03), and were more likely to receive a carbapenem or fluoroquinolone antibiotic (P < .00001), which may have implications on selection of more antimicrobial resistance or C. difficile infections [23]. From an economic standpoint, a recent comprehensive meta-analysis showed that reported penicillin-allergic patients had higher outpatient and inpatient drug costs and inpatient hospitalizations that cost on average $1145-$4254 more per patient [24].…”
Section: Adverse Outcomes In Patients Allergic To Penicillinmentioning
confidence: 99%